Mass spectrometry for serine ADP-ribosylation? Think o-glycosylation!. Issue 11 (18th May 2017) - Bonfiglio, Juan J.; Colby, Thomas; Matic, Ivan
Abstract: Protein ADP-ribosylation (ADPr), a biologically and clinically important post-translational modification, exerts its functions by targeting a variety of different amino acids. Its repertoire recently expanded to include serine ADPr, which is emerging as an important and widespread signal in the DNA damage response. Chemically, serine ADPr (and more generally o-glycosidic ADPr) is a form of o-glycosylation, and its extreme lability renders it practically invisible to standard mass spectrometry approaches, often leading to erroneous localizations. The knowledge from the mature field of o-glycosation and our own initial difficulties with mass spectrometric analyzes of serine ADPr suggest how to avoid these misidentifications and fully explore the scope of o-glycosidic ADPr in DNA damage response and beyond.